Participation Patterns and Program Impacts of Hawaii's JOBS WORKS! Demonstration Project - Olson, Jerome A.; Schexnayder, Deanna T.; O'Shea, Daniel P.; Texas Univ., Austin. Lyndon B. Johnson School of Public Affairs ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
A study of Hawaii's JOBS WORKS! waiver demonstration project determined its influence on participant self-sufficiency and receipt of Aid to Families with Dependent Children (AFDC). Hawaii received a waiver to lift the 8-week federal limitation on upfront job search, operate on less than a statewide basis, require 18 hours of work, and secure matched federal funds for implementation. About 6,000 individuals in the Job Opportunities and Basic Skills Program (JOBS) were randomly assigned to experimental or control groups. JOBS WORKS! offered immediate job search and readiness activities and job development and placement services to AFDC recipients waiting for openings in JOBS activities. Data were from administrative records of the Hawaii Departments of Human Services and of Labor and Industrial Relations. Self-sufficiency measures included employment rates, length of employment, amount of total earnings, and total family income. AFDC measures included average amount of benefits, exit and recidivism rates, use of subsidized child care, and rates at which persons were sanctioned for failing to comply with program requirements. Results indicated that rates and length of employment and total earnings were significantly higher for the experimental group. Experimental members experienced a 6.3 percent net decrease in average AFDC benefits and left the rolls at significantly higher rates. However, the experiment had no significant effect on rates of AFDC recidivism. (Statistical methods and detailed results are appended.) (YLB)
Sponsoring Agency: Hawaii State Dept. of Human Services, Honolulu.
Contract Number: DHS-96-SSSSD-4925.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Demonstration Programs; Employment Patterns; Employment Programs; Federal Legislation; Income; Job Placement; Job Training; Program Effectiveness; Program Evaluation; State Programs; Welfare Recipients; Welfare Services; Hawaii -- Job Opportunities and Basic Skills Program; Reports, Research